Measurements of long-range azimuthal anisotropies and associated Fourier coefficients for pp collisions at s√=5.02 and 13 TeV and p+Pb collisions at sNN−−−√=5.02 TeV with the ATLAS detector - Aaboud, M. (2016)
ATLAS measurements of two-particle correlations are presented for √ s = 5.02 and 13 TeV pp collisions and for √ sNN = 5.02 TeV p+Pb collisions at the LHC. The correlation functions are measured as a function of relative azimuthal angle ∆φ, and pseudorapidity separation ∆η, using charged particles detected within the pseudorapidity interval |η|<2.5. Azimuthal modulation in the long-range component of the correlation function, with |∆η|>2, is studied using a template fitting procedure to remove a “back-to-back” contribution to the correlation function that primarily arises from hard-scattering processes. In addition to the elliptic, cos (2∆φ), modulation observed in a previous measurement, the pp correlation functions exhibit significant cos (3∆φ) and cos (4∆φ) modulation. The Fourier coefficients vn,n associated with the cos (n∆φ) modulation of the correlation functions for n = 2–4 are measured as a function of charged-particle multiplicity and charged-particle transverse momentum. The Fourier coefficients are observed to be compatible with cos (nφ) modulation of per-event single-particle azimuthal angle distributions. The single-particle Fourier coefficients vn are measured as a function of charged-particle multiplicity, and charged-particle transverse momentum for n= 2–4. The integrated luminosities used in this analysis are, 64 nb−1 for the √ s = 13 TeV pp data, 170 nb−1 for the √ s = 5.02 TeV pp data and 28 nb−1 for the √ sNN = 5.02 TeV p+Pb data.